2022
DOI: 10.3389/fpsyt.2022.800687
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trauma: Conceptual framework, associated risks and comorbidities, and evaluation and treatment

Abstract: Children exposed to adverse childhood experiences (ACEs) and pervasive interpersonal traumas may go on to develop PTSD and, in most cases, will further undergo a significant shift in their developmental trajectory. This paper examines contemporary research on Developmental Trauma (DT), which is inextricably linked to disruptions in social cognition, physiological and behavioral regulation, and parent-child attachments. Developmental trauma associated with early experiences of abuse or neglect leads to multi-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 211 publications
2
15
0
1
Order By: Relevance
“…18 Research has shown that posttraumatic stress disorder (PTSD) is the most common psychiatric disorder occurring after a traumatic event (or after ACEs) in both young people and adults. 19,20 PTSD is a major chronic psychiatric condition formally recognized in 1980. 21 PTSD may occur 1 month after a direct or indirect exposure to a traumatic event, which is defined as a life-threatening condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Research has shown that posttraumatic stress disorder (PTSD) is the most common psychiatric disorder occurring after a traumatic event (or after ACEs) in both young people and adults. 19,20 PTSD is a major chronic psychiatric condition formally recognized in 1980. 21 PTSD may occur 1 month after a direct or indirect exposure to a traumatic event, which is defined as a life-threatening condition.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that posttraumatic stress disorder (PTSD) is the most common psychiatric disorder occurring after a traumatic event (or after ACEs) in both young people and adults . PTSD is a major chronic psychiatric condition formally recognized in 1980 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, chronic exposure to childhood traumatic events is closely associated with an elevated likelihood of developing Complex Post-traumatic Stress Disorder (cPTSD) [ 3 ]. Indeed, cPTSD has gained recognition as a novel diagnosis in the Eleventh International Classification of Diseases (ICD-11) [ 4 , 5 ]. The proposition of a repeated trauma-related disorder, as articulated by Herman, underscores the potentially profound impact of prolonged traumatic stressors, particularly on self-organization, with a focus on the affective and relational domains [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…cPTSD often ensues from unstable and distressing environmental contexts that negatively impact a child’s self-regulation skills, emotional equilibrium, psychological well-being, and interpersonal bonds [ 9 ]. Notably, particular attention has been devoted to the manifestation of self-organization disorders (DSO) observed within this condition, encompassing symptomatology spanning affective dysregulation, negative self-concept, and disrupted relationships [ 4 ]. Dysregulation, in this scenario, is a state of distress or impairment associated with the inability to tolerate aspects of one’s internal experience, including emotions, thoughts, bodily sensations, and physiological arousal.…”
Section: Introductionmentioning
confidence: 99%
“…Не виникає сумнівів, що означені негаразди призводять до виникнення численних проблем із психічним та соматичним здоров'ям. Посттравматичний стресовий розлад (ПСР) лежить в основі погіршення загального стану здоров'я, появи різноманітних скарг, загострення вже наявних в анамнезі дитини хвороб, нашаровування інших патологій із розвитком коморбідних станів [6,7].…”
unclassified